Antibacterial activity and mechanism of linalool against Pseudomonas aeruginosa. (April 2020) - Liu, Xue; Cai, Jiaxin; Chen, Haiming; Zhong, Qiuping; Hou, Yaqi; Chen, Weijun; Chen, Wenxue
Abstract: The purpose of this study was to evaluate the antibacterial activity and mechanism of linalool against Pseudomonas aeruginosa . The determination of antibacterial activity was based on the minimum inhibitory concentration (MIC) and the minimum bactericide concentration (MBC). Further, the antibacterial mechanism was explored by a growth curve assay, scanning electron microscopy (SEM), cell membrane permeability, membrane potential and respiratory chain dehydrogenase determination. The MIC and the MBC of linalool were 431 μg/mL and 862 μg/mL, respectively. The growth curve assay showed that the growth of P. aeruginosa was inhibited. The results of SEM revealed that linalool disrupted the normal morphology of the cell. The release of nucleic acids as well as the decrease in the membrane potential proved that the membrane integrity of P. aeruginosa was destroyed. Moreover, the respiratory chain was damaged by respiratory chain dehydrogenase determination as the absorbance at 490 nm decreased. This research suggested that it was possible for linalool to become a preservative of food by destroying the cell membrane, resulting in cell death. Graphical abstract: Image 1 Highlights: This paper determined the antibacterial activity of linalool against Pseudomonas aeruginosa. This paper studied the antibacterial mechanism of linalool against Pseudomonas aeruginosa. This paper provided the potential for linalool to become a preservative of food.